Chartering capitalism organizing markets, states, and publics - Erikson, Emily (Emerald, 2015)
Chartered companies, the organizational precursors to modern multinationals, acted as the primary vehicles behind the expansion of European political and economic hegemony, and were thus central to the creation of modern global political and economic institutions, and international trade and relations. This volume covers the evolution of the chartered company form, beginning with one of the earliest known chartered organizations, Casa di San Giorgio, founded in 1407. Also included are the Merchant Adventurers, the Levant Company, the English and Dutch East India Companies, Royal African Company, and Hudson's Bay Company. Collectively, the contributions employ comparative methods, archival research, case studies, statistical analyses, computational models, network analyses, and new theoretical conceptualizations to map out the complex interactions that took place within the companies between state and commercial actors in and across Europe, Asia, Africa, and the Americas interactions that renegotiated and ultimately institutionalized what were to become modern conceptions of public and private and defined many of the political and economic structures of capitalism.
Keywords: Political Science -- History & Theory.; Social Science -- Sociology -- General.; Social theory.; Capitalism -- Europe.; Commercial associations -- Europe.; elektronické knihy; electronic books